Self-concept and self-efficacy’s role in achievement motivation and physics learning outcomes - Arafah, Kaharuddin; Burhanuddin Arafah, Azhariah Nur B. Arafah, (Opción, 2020)
The aim of the study was to analyze the effect of self-concept and self-efficacy on achievement motivation and physics learning outcomes. The samples of the study were 126 students taken by means of the Sloven technique using questionnaires and test results of physics learning. The data of test results were analyzed by using Structural Equation Modeling with AMOS software. As a result, self-concept and self-efficacy have a direct positive effect on student’s motivation achievement. In conclusion, the teacher also must investigate and analyze the basic needs of the student in learning to achieve the objective of learning.